1998
DOI: 10.1300/j031v09n04_03
|View full text |Cite
|
Sign up to set email alerts
|

The Failed Patient Self-Determination Act and Policy Alternatives for the Right to Die

Abstract: The empirical evidence regarding the implementation and impact of the federal Patient Self-Determination Act is examined in this article. The Act was designed to increase the use of advance medical directives in light of the U.S. Supreme Court's Cruzan decision. Research shows that the law has had little effect and that the use of advance directives has scant relation to medical treatment and care. Various policy alternatives for the right to die are also examined. The authors conclude with an analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The United States Patient Self-Determination Act of 1990, probably the largest public effort for advocating ADs in the U.S., requires all hospitals to provide adults at the time of admission information about their rights regarding ADs [29]. While laudable, this process does little to promote advance care planning, which ideally is the result of a conversation between patients and their physicians prior to hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The United States Patient Self-Determination Act of 1990, probably the largest public effort for advocating ADs in the U.S., requires all hospitals to provide adults at the time of admission information about their rights regarding ADs [29]. While laudable, this process does little to promote advance care planning, which ideally is the result of a conversation between patients and their physicians prior to hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The federal government has sought to propagate living wills through the Patient Self‐Determination Act, 36 which essentially requires medical institutions to inform patients about advance directives. However, “empirical studies demonstrate that: the PSDA has generally failed to foster a significant increase in advance directives use; it is being implemented by medical institutions and their personnel in a passive manner; and the involvement of physicians in its implementation is lacking.” 37 One commentator even thinks “the PSDA's legal requirements have become a ceiling instead of a floor.” 38…”
Section: Do People Have Living Wills?mentioning
confidence: 99%
“…Although the intention of advance directives is good, previous investigators reported that many medical staffs have insufficient understanding of such directives and that there is a low rate of chart documenting of living wills, even after advance directives had been established for many years in the United States 4 5. Additionally, ethical problems arose when advance directives were promoted and applied in different cultures 6.…”
mentioning
confidence: 99%